Analysis Election Smartphone Best for Students UIN Sunan Kalijaga Using The Analytic Hierarchy Process (AHP) Method - Maarif, Ikhsan Syamsul; Candra, Aghnan; Fadilah, Isnaini Nur; Aisyah, Siti (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2025)
The rapid development and advancement of digital technology has driven major changes in human life, including the use of technological devices such as smartphones. With the increasing need for smartphones to support academic activities, consumers sometimes face difficulties in determining choices that suit their needs. This study aims to identify smartphone features that are most considered by students in the purchasing decision-making process, using the Analytical Hierarchy Process (AHP) method. This study uses primary data obtained through questionnaires to active students with criteria used as a basis for comparison including price, storage capacity, camera quality, processor, and design. The results of the study show that the storage capacity feature is the main consideration in choosing a smartphon, followed by the processor feature and camera quality. Price and design are ranked next. This finding shows that the need for performance and efficiency in support activity academic become priority main for students. In conclusion, the results of this study can be a reference for students in determining their choice of smartphone. Which in accordance with need academic as well as provide manufacturers with an overview of current consumer preferences.